(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Cybersecurity plays an important role in the world of information technology. Securing data is one of the biggest challenges today. The first thing that comes to mind when we think of cybersecurity is cybercrime, which is growing by the day. The vast potential of the virtual space is being used not only for peaceful purposes, but also for the implementation of threats of various kinds and degrees. Such threats are not limited to fraud, passwords to bank accounts, and theft of personal information. Threats to the Internet, not only for the money of users, but also for their lives, are growing. This article contains the necessary ideas for the prevention of cybercrime in our country, compliance with the rules of cybernetics, ensuring the peace and security of our citizens, protection from cyber attacks in the virtual world.